2009
DOI: 10.4161/auto.5.1.7175
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-assisted glycogen catabolism regulates asexual differentiation inMagnaporthe oryzae

Abstract: Autophagy, a conserved pathway for bulk cellular degradation and recycling in eukaryotes, regulates proper turnover of organelles, membranes and certain proteins. Such regulated degradation is important for cell growth and development, particularly during environmental stress conditions, which act as key inducers of autophagy. We found that autophagy and MoATG8 were significantly induced during asexual development in Magnaporthe oryzae. An RFP-tagged MoAtg8 showed specific localization and enrichment in aerial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
139
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(143 citation statements)
references
References 52 publications
(77 reference statements)
4
139
0
Order By: Relevance
“…3D). The N-terminal RFP tag was likely cleaved from the RFP-Atg8 fusion protein and accumulated in the vacuoles upon nitrogen starvation, 10 indicating proper fusion of autophagosomes with the vacuole in snx41D. This result further supported the conclusion that autophagy was active and functional in the snx41D mutant.…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…3D). The N-terminal RFP tag was likely cleaved from the RFP-Atg8 fusion protein and accumulated in the vacuoles upon nitrogen starvation, 10 indicating proper fusion of autophagosomes with the vacuole in snx41D. This result further supported the conclusion that autophagy was active and functional in the snx41D mutant.…”
Section: Resultssupporting
confidence: 77%
“…We had earlier reported that autophagyassisted glycogen catabolism is necessary for Magnaporthe conidiation, but could be bypassed by exogenous supplementation with sucrose or glucose 6-phosphate (G6P) in the atg8D mutant. 10 External addition of sucrose or G6P could also suppress the conidiation defects in another autophagy-deficient mutant, atg1D (Fig. S3A), further confirming the importance of glycogen autophagy in carbon homeostasis during Magnporthe conidiation.…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations